2022
DOI: 10.1002/jha2.465
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 outcomes in haematopoietic cell transplant recipients: A systematic review and meta‐analysis

Abstract: Up‐to‐date information on coronavirus disease 2019 (COVID‐19) outcomes and risk factors in haematopoietic cell transplantation (HCT) recipients is required to inform on decisions about cancer treatment and COVID‐19 mitigation strategies. We performed a meta‐analysis to address this knowledge gap. All studies with at least five patients who reported COVID‐19‐related deaths in HCT recipients were included. The primary outcome was COVID‐19‐related death. Secondary outcomes were COVID‐19‐related mechanical ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, this study is the first among COVID-19 HSCT patients to demonstrate an independent association between mechanical ventilation and chest CT involvement at diagnosis with death 1,4,6,[13][14][15][16][17][18][19] . In another meta-analysis, a subgroup analysis revealed a higher risk of death among patients who develop COVID-19 within 12 months of HSCT and in those with GVHD using immunosuppressant drugs 3 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first among COVID-19 HSCT patients to demonstrate an independent association between mechanical ventilation and chest CT involvement at diagnosis with death 1,4,6,[13][14][15][16][17][18][19] . In another meta-analysis, a subgroup analysis revealed a higher risk of death among patients who develop COVID-19 within 12 months of HSCT and in those with GVHD using immunosuppressant drugs 3 .…”
Section: Discussionmentioning
confidence: 98%
“…A limited number of studies have reported COVID-19 outcomes in the HSCT setting [3][4][5][6] . The objective of this study was to describe COVID-19 burden in a cohort of HSCT recipients who were hospitalized in São Paulo, Brazil during three years of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…19 More recently, a meta-analysis of 26 studies which included 2141 HCT recipients showed that the incidence of ICU admission and mechanical ventilation was 18% and 14% respectively, while COVID-19-related death occurred in 21% (95% CI 18%-24%). 20 Outcomes do not appear to be substantially different in allogeneic and autologous HCT-recipients. 16,18 Despite some differences reported in smaller studies, 10,[21][22][23] survival was similar in the two groups at 4 weeks (67%-68%) in one study 17 and 6 weeks (approximately 75%) in another.…”
Section: Hct Recipientsmentioning
confidence: 97%
“…Age above 50, presence of three or more comorbidities, active hematologic disease, COVID‐19 occurring with 12 months from HCT, and severe/critical infection were all independently associated with increased mortality 19 . More recently, a meta‐analysis of 26 studies which included 2141 HCT recipients showed that the incidence of ICU admission and mechanical ventilation was 18% and 14% respectively, while COVID‐19‐related death occurred in 21% (95% CI 18%–24%) 20 …”
Section: Clinical Outcomes Of Covid‐19mentioning
confidence: 99%
“…Some scarce studies have shown that the prognosis of HSCT recipients with COVID-19 infection is worse than that of the general population 11 , 12 and especially in cases of active GVHD 13 . To our knowledge, no data exist regarding the impact of SARS-CoV-2 on PFT in HSCT patients.…”
Section: Casementioning
confidence: 99%